O direito penal do inimigo e a concretização dos direitos fundamentais: um estudo sobre a presença da teoria de Günther Jakobs no ordenamento jurídico brasileiro - Moraes, Vinicius Borges de (Universidade do Vale do Rio do Sinos, 2009)
It has been observed, as much in practical field as in the scientific one, an attempt to readequate the criminal politics, this attempt is motivated by the new criminal modalities, in special, organized crime, narcotic traffic, economical crimes, and of course, terrorism. In quest for a better adequacy of the protection mechanisms, it seens to be necessary rethink the fundamental concepts of criminal sciences. Based in these studies rises the propose of one partial criminal law, more energetic and faster, based in the possibility of a flexibility of fundamental guarantees –material and process substance - of infractors, in delicts whose results has as characteristic put the social structures in risk. The Theory starts from the principle that this agents, through this conduct, would be rebelling them selves against the State, that could result in a negation to be citizen condition. Ahead to this, would this very State legitimated to treat them as enemy. In this context, the present investigation, using a “semi
Keywords: garantias fundamentais; política criminal; sociedade do risco; terrorismo; direito penal do inimigo; criminal politics; fundamental rights; society of the risk; terrorism; enemy criminal law; Ciências Sociais Aplicadas